EVOLUTIONARY DEVELOPMENT AND FUNCTIONAL STATE OF THE HYPOTHALAMIC-PITITUITARY SYSTEM (LITERATURE REVIEW) - Barno X. Shagazatova; Dilfuza M. Artikova; Jannat I. Islamova (Central Asian Journal of Medicine, 2024)
The hypothalamic-pituitary system of the human body is a complex neurosecretory complex that coordinates the endocrine regulation of metabolism with the work of the autonomic nervous system and the integral emotional and behavioral regulation of the limbic system. This review presents an analysis of the literature data, which indicates the entire path of development of the hypothalamic-pituitary system, nervous and humoral regulation of the body, the biological effect of hormones of the hypothalamus and pituitary gland, the physiology of the hypothalamic-pituitary system and diseases associated with a deficiency or excess of these hormones.